PENDEKATAN SASTRA DALAM PENAFSIRAN AL-QUR’AN (TELAAH PEMIKIRAN BINTI SYATY) - Hamka Hasan (JURNAL INDO-ISLAMIKA, 2019)
Binti Syaty is one of the Islamic scholars who focuses on the study of literature. This approach is also used to interpret the Qur'an - as the most authoritative source in Islam. She applies the literary method of her teacher and husband, Amin al-Khuli. In this paper the author will describe the literary approach used by Binti Syaty in interpreting Islamic sources - namely the al-Qur'an.